2017
DOI: 10.2140/apde.2017.10.1613
|View full text |Cite
|
Sign up to set email alerts
|

Analytic hypoellipticity for sums of squares and the Treves conjecture, II

Abstract: We are concerned with the problem of real analytic regularity of the solutions of sums of squares with real analytic coefficients. The Treves conjecture defines a stratification and states that an operator of this type is analytic hypoelliptic if and only if all the strata in the stratification are symplectic manifolds.Albano, Bove, and Mughetti (2016) produced an example where the operator has a single symplectic stratum, according to the conjecture, but is not analytic hypoelliptic.If the characteristic mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…More precisely in [2] and [3] the authors produced and studied the first models which are not consistent with the Treves conjecture, [13]. However, contrary to the cases of [2] and [3], the operators studied here have no exceptional strata because the symbols do not depend on the tangent variables of the "inner most" stratum. Our results can be stated as follows:…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…More precisely in [2] and [3] the authors produced and studied the first models which are not consistent with the Treves conjecture, [13]. However, contrary to the cases of [2] and [3], the operators studied here have no exceptional strata because the symbols do not depend on the tangent variables of the "inner most" stratum. Our results can be stated as follows:…”
Section: Introductionmentioning
confidence: 77%
“…In 1999 Treves formulated a conjecture which related the analytic hypoellipticity with geometrical properties of the characteristic variety of P , see [12] and [13]. In recent papers Albano, Bove and Mughetti, [2], and Bove and Mughetti, [3], showed that the sufficient part of the Treves' conjecture does not hold neither locally nor microlocally. More precisely in [2] and [3] the authors produced and studied the first models which are not consistent with the Treves conjecture, [13].…”
Section: Introductionmentioning
confidence: 99%
“…In [1,3] it was shown that the Treves conjecture does not hold by producing an example contradicting the conjecture. The example is the operator in (1.3).…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…They showed that even if P ABM has a single symplectic stratum, in meaning of the Poisson-Treves stratification, it is Gevrey hypoelliptic of order s = r(q − 1)[q − 1 + (r − 1)(p − 1)] −1 and not better. In [2] the authors investigated the following operator (1.2) P BM (x, D) = D 2 1 +x 2(r+ℓ−1) 1…”
Section: Introductionmentioning
confidence: 99%